2017
DOI: 10.1007/s11010-017-3120-z
|View full text |Cite
|
Sign up to set email alerts
|

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus

Abstract: Whether the Arg913Gln variation (rs11643718, G/A) of SLC12A3 contributes to diabetic nephropathy (DN) remains controversial. We undertook a case-control study to evaluate the association of the SLC12A3-Arg913Gln variation with the risk of end-stage renal disease (ESRD) in Chinese type 2 diabetes mellitus (T2DM) patients undergoing hemodialysis, and analyzed the genotype-phenotype interaction. Unrelated Chinese T2DM patients (n = 372) with diabetic retinopathy were classified into the non-DN (control) group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It regulates the reabsorption of sodium ions and chloride ions and is a pivotal point of maintaining electrolyte homeostasis and regulating arterial blood pressure [76]. A loss of NCC function is responsible for Gitelman syndrome, an autosomal recessive disorder characterized by low blood pressure, hypocalciuria, hypokalemic metabolic alkalosis, and hypomagnesemia.…”
Section: Other Susceptibility Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…It regulates the reabsorption of sodium ions and chloride ions and is a pivotal point of maintaining electrolyte homeostasis and regulating arterial blood pressure [76]. A loss of NCC function is responsible for Gitelman syndrome, an autosomal recessive disorder characterized by low blood pressure, hypocalciuria, hypokalemic metabolic alkalosis, and hypomagnesemia.…”
Section: Other Susceptibility Genesmentioning
confidence: 99%
“…Additionally, in a Korean population, SNPs and haplotypes of the SLC12A3 gene, especially Arg913Gln, were significantly associated with ESRD caused by DN [79]. A recent case-control study suggested that Arg913Gln was associated with a high risk of DN-ESRD in Chinese T2DM patients undergoing hemodialysis and that the GA+AA genotype may be related to increased blood pressure and urinary albumin excretion rate [76]. However, genetic variation at the SLC12A3 locus does not explain the risk of advanced DN among Caucasians and North Indian populations with T2D [80].…”
Section: Other Susceptibility Genesmentioning
confidence: 99%
“…[ 29 ] Mutation p.N359K is not the only SLC12A3 mutation associated with T2DM; mutation Arg913Gln of SLC12A3 has also been known to predict the development and progression of end-stage renal disease in Chinese T2DM patients. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients are often accompanied by abnormal lipid metabolism; therefore, hypertension and dyslipidemia are closely associated with each other and can affect each other’s morbidity. The second possibility is that recent studies have shown that in addition to hypertension and hyperlipidemia, SLC12A3 is also associated with type II diabetes [ 24 ] and obesity [ 25 ]. Several epidemiologic studies have shown that the co-existence of hypertension, and diabetes or obesity is due to common genetic and environmental factors such as diet, physical activity and age [ 26 ].…”
Section: Discussionmentioning
confidence: 99%